Institutional Response to Mining in Forest Reserves in Ghana: A Case Study of the Atewa Range Forest Reserve - Mensah-Odum, Nathaniel; Sarfo-Mensah, Paul; Antoh, Ernestina Fredua (British Journal of Healthcare and Medical Research, 2023)
Mineral exploration and utilization contribute to national development but threaten the environment. Besides, illegal mining in forest reserves has been a global concern due to its harm to environmental resources. Perhaps, the [formal and informal] institutional perspective on curbing this menace has been narrowly discussed. This study echoes recent discussions on unlawful mining activities in Ghana’s forest reserves, focusing on the Atewa Range Forest Reserve, as it explores the institutional partnership and potential roadblocks to fulfilling their mandates. A mixed study approach was employed. The study concluded that institutional networks to manage forest resources have been ineffective due to poor collaboration. This is mainly due to non-compliance with mineral laws by culprits as a result of the absence of key regulatory institutions at the local level. The study recommends that the establishment of key regulatory agencies at the local level could curb this menace.